Heart rate variability-derived thresholds for exercise intensity prescription in endurance sports: A systematic review of interrelations and agreement with different ventilatory and blood lactate thresholds. - Kaufmann, S.; Gronwald, T.; Herold, F. (Sports Medicine - Open, 2023)
Key Points